Does the use of platelet-rich fibrin enhance the rate of orthodontic tooth movement? A systematic review and meta-analysis - Jitendra Sharan; Indumathi Shivakumar; Arunachalam Shivakumar; Vineet Kumar Kamal; Prabhat Kumar Chaudhari; Srikrishna Challasany; Anand Marya (Journal of Oral Biology and Craniofacial Research)
Introduction: This review synthesizes the available evidence pertinent to the effect of platelet-rich fibrin on the rate of orthodontic tooth movement during comprehensive orthodontic treatment. Method: This review followed the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines. Nine electronic databases were searched until January 2024 without restrictions, followed by a hand search of the reference lists. Controlled randomized split-mouth human studies assessing the effect of platelet-rich fibrin on the rate of orthodontic tooth movement were included. All relevant data from the included studies were extracted and pooled for qualitative and quantitative analysis. Risk-of-Bias was assessed using the Cochrane Risk of Bias tool. The certainty of the evidence was graded using the Grading of Recommendations, Assessment, Development, and Evaluation tool. Results: From 515 studies, eleven randomized clinical trials were included for qualitative analysis and nine for quantitative analysis. The certainty of the evidence for these studies was low to moderate. The overall risk of bias for most studies was of some concern. The pooled estimate of the data from ten studies has a mean revealed difference of 1.31 (0.13–2.48) at a 95 % confidence interval with significant heterogeneity. Conclusions: This systematic review suggest that platelet-rich fibrin enhances the orthodontic tooth movement rate, but the evidence quality was moderate. Further, based on the currently available evidence, the effectiveness of platelet-rich fibrin on the acceleration of orthodontic tooth movement could not be fully established. Trial registration: PROSPERO: (CRD42021261836).